The Study of the Occurrence of Food Allergy in Students and its Prevention with the Help of Health Physical Training (Czech Journal of Multidisciplinary Innovations, 2022)
During the last decades there has been a constant increase in a number of allergicdiseases all over the world. The high urgency of the problem of allergy prevention is due to thefact that the frequency of occurrence of allergies, especially among young people, is rapidlyincreasing year by year.This research paper is devoted to one of the most urgent and actual problems of our time – theproblem of preventing the appearance of food allergies among young people.As part of the study, the authors consider the concept and essence of food allergy, the maincauses and factors that provoke its occurrence in the student age category, and offer the mainmethods of preventing this disease using recreational physical education.The research paper presents the results of a sociological study conducted along with the studentsof the Medical Faculty of the Gulistan State University of the Republic of Uzbekistan